Synthesis, Physicochemical Properties, and Antimicrobial Studies of Iron (III) Complexes of Ciprofloxacin, Cloxacillin, and Amoxicillin. (19th November 2014) - Eze, Fabian I.; Ajali, Uzoechi; Ukoha, Pius O.
Abstract : Iron (III) complexes of ciprofloxacin, amoxicillin, and cloxacillin were synthesized and their aqueous solubility profiles, relative stabilities, and antimicrobial properties were evaluated. The complexes showed improved aqueous solubility when compared to the corresponding ligands. Relative thermal and acid stabilities were determined spectrophotometrically and the results showed that the complexes have enhanced thermal and acid stabilities when compared to the pure ligands. Antimicrobial studies showed that the complexes have decreased activities against most of the tested microorganisms. Ciprofloxacin complex, however, showed almost the same activity as the corresponding ligand. Job's method of continuous variation suggested 1 : 2 metals to ligand stoichiometry for ciprofloxacin complex but 1 : 1 for cloxacillin complex.